Physics, Chemistry and Biology Student Teachers' Understandings of Nanotechnology - Kurnaz, Mehmet Altan; Alev, Nedim; Pektaş, Murat; Bayraktar, Güntaç (Procedia - Social and Behavioral Sciences 191 ( 2015 ) 1767 – 1771, 2012)
The aim of this study is to determine student teachers’ understandings of nanotechnology. The study was conducted as a case study method. The participant of the study comprised 85 candidate physics (33), chemistry (16) and biology (36) teachers in the Faculty of Education at a university in Black Sea Region in Turkey. To reach the aim of the study, an achievement test with some open ended questions was formed. The answers from the student teachers were analysed using the content analysis method. The data analysis revealed that majority of the questions were responded as ‘I don’t know’ by the student teachers. It was also determined that the student teachers did not scientifically conceptualize “nanotechnology” as expected, and they did not give scientifically accepted examples of nanotechnology. In the light of the findings, the study was highlighted that the student teachers had non-scientific understandings for the nanotechnology. As a consequence of this study, it is thought that the results of this study will be helpful to curriculum developers, researchers and teachers.
Keywords: nanotechnology, student teachers, understandings.